(untitled) (mathematica didactica, 2023)
An important basis for the development of flexible mental calculation is the ability to internalize and retrieve selected central contents of elementary school mathematics that have been acquired in an understanding-oriented way. It is recommended to implement automatization practices such as "Blitzrechnen" as partner work. In our single-case study, we investigate to what extent students with mathematical learning difficulties benefit from the implementation of "reciprocal peer tutoring". The findings of both single-cases Alea and Taira demonstrate changes in the number of solving tasks, in determining quantities, number decomposition, and simple addition that can indicate a higher solution speed.